Day Of The Week Effect dan Implikasinya terhadap Investor - Hesti Murwaniputri; Donny Tupamahu; Rhidho Achyatul Havitz (Jurnal Manajemen dan Bisnis, 2023)
This study aims to find out whether there is a Day of the week effect on stock trading, and what are the implications of the day-of-the-week effect for investors in Jayapura City. The sample for this research is a company that is included in IDX80 for the period February 2021-January 2022. The data analysis method uses Kruskal Wallis and Man Whitney. The results of the study found that the day-of-the-week effect occurred on stocks included in the IDXV80 period from February 2021-January 2022. There was no Monday effect on stocks included in the IDXV80 period from February 2021-January 2022. There was a weekend effect on stocks included in the IDXV80 period from February 2021-January 2022, young investors in Jayapura City have not used the anomalies in the capital market as momentum for making investment decisions.